GAMBARAN TINGKAT PENGETAHUAN MAHASISWA PSKPS FK ULM ANGKATAN 2020 TENTANG FAKTOR RISIKO NOISE-INDUCED HEARING LOSS (NIHL) - Budiarman, Andi Azizah Maulidia; Asnawati, Asnawati; Huldani, Huldani; Kaidah, Siti; Rahmiati, Rahmiati (Homeostasis, 2024)
Abstract: A study conducted among 2020 cohort students at the Faculty of Medicine, ULM, aimed to evaluate their understanding of Noise-Induced Hearing Loss (NIHL) risk factors. NIHL, a hearing impairment caused by prolonged exposure to loud noise, is increasingly prevalent among adolescents due to excessive electronic media use. Employing a descriptive approach with a cross-sectional design, the study utilized total sampling, involving 154 respondents. Data collection relied on questionnaires and analysis via Microsoft Excel. Results indicated that 55.8% of participants had moderate knowledge, 40.2% demonstrated good understanding, and 3.8% exhibited poor knowledge about NIHL risk factors. The average knowledge score was 72.13, placing it in the moderate category. This denotes an overall moderate level of awareness among the students. In conclusion, the research highlighted the prevailing moderate understanding among the 2020 cohort students at the Faculty of Medicine, ULM, regarding NIHL risk factors. The findings emphasize the need for increased education and awareness programs to address this concerning issue, particularly among young individuals frequently exposed to potentially harmful noise from electronic devices. Keywords: Knowledge Level, medical students, NIHL. Abstrak: Noiced-Induced Hearing Loss (NIHL) merupakan gangguan pendengaran dan ketulian akibat terpajan bising yang cukup keras dalam jangka waktu yang lama. Pada remaja, penggunaan media elektronik yang berlebihan menjadi penyebab utama terjadinya NIHL. Penelitian ini bertujuan untuk mengetahui gambaran tingkat pengetahuan mahasiswa PSKPS FK ULM angkatan 2020 tentang faktor risiko Noise-Induced Hearing Loss (NIHL). Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross sectional. Pemilihan sampel menggunakan teknik total sampling, didapatkan 154 orang responden. Teknik pengumpulan data menggunakan kuesioner. Data diolah menggunakan Microsoft Excel. 55.8% responden memiliki tingkat pengetahuan yang cukup, 40.2% responden memiliki tingkat pengetahuan yang baik, dan 3.8% responden memiliki tingkat pengetahuan yang kurang. Rata-rata nilai pengetahuan responden adalah 72.13 yang termasuk kategori Dapat disimpulkan secara umum tingkat pengetahuan mahasiswa PSKPS FK ULM angkatan 2020 tentang faktor risiko Noise-Induced Hearing Loss (NIHL) tergolong dalam kategori cukup. Kata kunci: Tingkat pengetahuan, mahasiswa kedokteran, NIHL.